Anticancer Drugs - O'Boyle, Niamh M (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The past decades have seen major developments in the understanding of the cellular and molecular biology of cancer. Significant progress has been achieved regarding long-term survival for the patients of many cancers with the use of tamoxifen for treatment of breast cancer, treatment of chronic myeloid leukaemia with imatinib, and the success of biological drugs. The transition from cytotoxic chemotherapy to targeted cancer drug discovery and development has resulted in an increasing selection of tools available to oncologists. In this Special Issue of Pharmaceuticals, we highlight the opportunities and challenges in the discovery and design of innovative cancer therapies, novel small-molecule cancer drugs and antibody-drug conjugates, with articles covering a variety of anticancer therapies and potential relevant disease states and applications. Significant efforts are being made to develop and improve cancer treatments and to translate basic research findings into clinical use, resulting in improvements in survival rates and quality of life for cancer patients. We demonstrate the possibilities and scope for future research in these areas and also highlight the challenges faced by scientists in the area of anticancer drug development leading to improved targeted treatments and better survival rates for cancer patients.